Performance Analysis of Officers Reviewing from Motivation, Awards and Work Coordination on Health Officers at Public Health Center Lenteng, Sumenep Regency - Yuly Peristiowati; Edi Kurnianto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Performance or work performance is the result of a performance appraisal made by his immediate supervisor to be used as material for work improvement, compensation adjustments, placement decisions, development needs and more.The purpose of this study is to analyze the influence of motivation, appreciation and work coordination on the performance of health workers at the Lenteng Health Center, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of motivation, appreciation and work coordination on the performance of health workers at the Lenteng Health Center, Sumenep Regency. The total population is 146 respondents and a sample of 107 respondents is taken by using Simple Random Sampling technique. In the study, it was found that most of the respondents had a high category of motivation as many as 56 respondents (52%). Almost half of the respondents had sufficient category awards as many as 48 respondents (45%). Most of the respondents have coordination in the good category as many as 56 respondents (52%). Most of the respondents have a good performance category as many as 58 respondents (54%). Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that there is a simultaneous influence of motivation, appreciation and coordination of work on the performance of health workers at the Lenteng Public Health Center, Sumenep Regency with an effect of 84.3%. It is hoped that health workers are able to be more oriented to the work itself in providing results, impacts, and benefits for the community and for other employees by increasing motivation, not complaining, coordinating with each other and improving performance.